1995
DOI: 10.1177/088840649501800205
|View full text |Cite
|
Sign up to set email alerts
|

Educator Preferences of Accommodations for Students with Attention Deficit Hyperactivity Disorder

Abstract: The purpose of this study was to assess the accommodation practices and preferences of general, special, and resource educators for working with students with AD/HD. Participants included 129 teachers representing 10 schools. Findings indicated that full-time special educators tried and succeeded with more accommodations than general educators, who in turn were more successful and less resistant than part-time teachers (e.g., specials). Secondary more than elementary teachers felt successful with techniques re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 13 publications
5
18
1
Order By: Relevance
“…In contrast to the above findings, Zentall and Stormont-Spurgin (1995) reported that there were no significant differences between general and special educators in the extent to which they had ''tried and succeeded'' implementing accommodations related to ''changing standards'', ''instructional methods'', ''classroom structure'', and ''consequences'' for students with ADHD. Stang et al (2008) also found no significant differences between general and special educators in the frequency with which they reported providing their students with instruction in self-determination strategies (e.g., goal-setting, selfmanagement).…”
Section: Relations Between Teacher Role and Instructional And Behaviocontrasting
confidence: 50%
“…In contrast to the above findings, Zentall and Stormont-Spurgin (1995) reported that there were no significant differences between general and special educators in the extent to which they had ''tried and succeeded'' implementing accommodations related to ''changing standards'', ''instructional methods'', ''classroom structure'', and ''consequences'' for students with ADHD. Stang et al (2008) also found no significant differences between general and special educators in the frequency with which they reported providing their students with instruction in self-determination strategies (e.g., goal-setting, selfmanagement).…”
Section: Relations Between Teacher Role and Instructional And Behaviocontrasting
confidence: 50%
“…The results also indicated that years of teaching experience, educational level, and the presence of a child with AD/HD in the classroom were not significantly related to intervention ratings. Our findings support previous research with older children that has found that years of teaching experience was not related to the acceptability of different intervention options (Power et al, 1995), beliefs regarding intervention effectiveness (Hawkins et al, 1991), or with intervention preferences (Zentall & Stormont-Spurgin, 1995).…”
Section: Discussionsupporting
confidence: 90%
“…All of the items were taken from the School Modifications Assessment Checklist (SMAC), which has been used in past research with school-aged children (Zentall & Stormont-Spurgin, 1995). This scale was used to assess subjective perceptions of importance and comfort levels of preschool teachers when presented with interventions for students with AD/HD.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations